Postoperative Survival in Gastric Cancer Patients and its Associated Factors: A Time Dependent Covariates Model - H Zeraati; M Mahmoudi; A Kazemnejad; K Mohammad (Tehran University of Medical Sciences, 2006)
The gastric cancer in Iran is the fourth in the general population. This study was designed to determine the five-year survival rate of gastric cancer patients, and to assess its associated factors. We analyzed the data using a time-dependent covariates model, and recommend it for analyses of similar data. 281 gastric cancer patients with adenocarcinomatous pathology who had been operated on at the Iran Cancer Institute between 1995 and 1999 were enrolled in this study. The patients' survival after surgery was determined, and its relationship with other variables were assessed. Kaplan-Meier, Cox and Breslow method were used, and an alpha level of 0.05 was considered significant. The five-year survival rate and the median life expectancy were 22.6% and 19.00 months, respectively. The Cox model showed that age, lymph node metastasis, recurrence, and disease stage influenced the chances of survival. It was also shown that lymph node metastasis and disease stage correlated with time of relapse, while age, distant metastasis and disease stage affected survival after relapse, and age correlated with survival of patients without recurrence. Gastric cancer patients in Iran have a low five-year survival rate. One of the most important reasons seems to be delayed consultation and diagnosis.